Understanding public support for workplace diversity and antidiscrimination policies in Europe - Blommaert, Lieselotte; Coenders, Marcel (Frontiers in Sociology, 2024)
Societal processes and public opinion can affect whether employers take action and which policy measures they choose to boost diversity, equal opportunities and inclusion, and to reduce discrimination in the workplace. Yet, public opinion regarding workplace diversity initiatives has so far received little scholarly attention, especially in Europe. Consequently, we have very little evidence about how the general public feels about workplace diversity policies – particularly those that are more often implemented or discussed in Europe – and about which factors shape public support for workplace diversity initiatives. Yet, a better understanding of the patterns and antecedents of citizens’ attitudes towards workplace diversity policies is of clear scientific and practical importance. Against this background, this study sheds light on public attitudes towards three different, commonly applied types of workplace diversity policies, and examines which individual-level and – innovatively – national-level conditions shape public support. To do so, we bring together insights from various different and so far largely disconnected strands of research and a range of theoretical perspectives. We use large-scale, representative survey data from two pooled waves of the Eurobarometer, covering 38,009 citizens across 26 European countries. We enrich these data with information on national-level income inequality as well as countries’ labor market and antidiscrimination legislation and policies, obtained from Eurostat and the Migrant Integration Policy Index (MIPEX). Results show significant differences in public support across the three types of policies, with the strongest support for diversity training, followed closely by monitoring recruitment procedures, whereas support for monitoring workforce composition is clearly lower. This is in line with the idea that support tends to be lower for more preferential and prescriptive workplace policies. Furthermore, we find that, in addition to individual-level factors – particularly gender, ethnic minority group membership, personal experiences with discrimination, prejudice, intergroup contact and political orientation – national-level conditions are important antecedents of public support for workplace diversity policies. That is, differences in public attitudes regarding such policies are also shaped by country-level income inequalities, people’s perceptions of how widespread discrimination and unequal opportunities are in society, and national-level laws and policies to fight unequal opportunities.